A case study on the clothing preferences of selected children with tactile defensiveness sensory issues - Balbin, Dana Beatrice Alonzo; Rayala, Maria Monica E. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT This research is about children who experience sensory-based clothing sensitivity due to Tactile Defensiveness (TD) wherein negative emotional and behavioral responses are triggered from certain types of tactile stimuli such as garment attributes of clothing which most people would find normal. TD is a type of Sensory Processing Disorder (SPD) which refers to the difficulty in processing sensory input due to an irregularity in brain function. The objective was to study clothing preferences of selected children with TD sensory issues. It aimed to answer how garment attributes contribute to these clothing preferences and to describe their corresponding behavior. The study utilized a case study method on three (3) children, aged fifteen, nine and four, who have been experiencing sensory issues related to TD and specifically experiencing clothing sensitivity. Through interviews with parents, clothing preferences of these children were identified along with their behaviors related to clothing sensitivity. Specific garment attributes were analyzed according to the set objectives. For a child with sensory-related clothing sensitivity, there are some behaviors that vary significantly from those with normal sensitivity. He can only wear certain types of clothing which provide him with the comfort performance he is looking for. He displays a noticeable feeling of distressed when he wears clothing that did not match his preference. Considerations in varying conditions, tolerance capabilities, and age when therapy intervention started were also recognized. The study would be beneficial to the academe and research institutions as platform reference for further research on sensory-related clothing sensitivity of Filipino children with the goal of ultimately helping and improving their quality of life through clothing comfort. The study could be further improved with more children to be observed and by conducting an actual wear test observation to have first hand information.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Children's clothing -- Philippines; Tactile agnosia